2017
DOI: 10.1071/py16012
|View full text |Cite
|
Sign up to set email alerts
|

Reducing emergency department presentations among chronically ill patients in Western Sydney: a key role for coordinated primary care

Abstract: Coordination of health services is thought to improve health outcomes for patients with chronic and complex illness; however, there is limited quantitative evidence for the effectiveness of coordinated care programs. HealthOne Mount Druitt (HOMD) is a coordinated care program operating in a disadvantaged area of Western Sydney, Australia. It operates as a combination 'virtual' and 'hub and spoke' model, with care coordination provided by liaison nurses. We aimed to determine whether there were changes in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…This coordinator role linked to improved collaboration has been recognised in other studies (e.g. Aspinal et al, 2012; Karam et al, 2018; Mallit et al, 2017; Prasad et al, 2014). In the Conditions, dimension nurses suggested that collaboration learning opportunities were insufficient.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…This coordinator role linked to improved collaboration has been recognised in other studies (e.g. Aspinal et al, 2012; Karam et al, 2018; Mallit et al, 2017; Prasad et al, 2014). In the Conditions, dimension nurses suggested that collaboration learning opportunities were insufficient.…”
Section: Discussionmentioning
confidence: 65%
“…In this collaboration, the nurses value and understand their own roles, responsibilities and work environment as well as those in partnership (Emich, 2018; Lemetti et al, 2015, 2017; Moore et al, 2019; Morley & Cashell, 2017). There are some specific nurses' roles reported in the literature, requiring these collaboration skills including, discharge coordination (Lemetti et al, 2017) and liaison nursing roles (Mallit et al, 2017; Pittman & Forrest, 2015; Ribas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A SCIPPS evaluation of a New South Wales Ministry of Health program, which was designed to better coordinate such care through a specialist liaison nurse role, showed promise. 33,34 GPs, community health centre staff and management all reported improved coordination of services, and better integrated health and social care. 35,36 Defined, but flexible, policy aims and objectives assisted in establishing and meeting local needs and priorities.…”
Section: Implications For Australian Gpsmentioning
confidence: 99%
“…There is a growing body of evidence that in order to be effective, in-depth interventions are required [ 1 ]. Intervention should reach beyond the traditional boundaries of intra-hospital care to embrace multi-disciplinary case management, providing care which is proactive and which is planned and delivered in the community [ 8 9 10 ]. Further, the case has been made for collaborative, whole system care in which navigation of both the medical and social sectors is required.…”
Section: Introductionmentioning
confidence: 99%